Teacher's contributions for the learning of written acts - Kohle, Erika Chrsitina [UNESP]; Miller, Stela [UNESP]; Silva Clarindo, Cleber Barbosa da [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2018)
This article aims to discuss the teacher's contributions to the learning of writing acts from the textual production work of sixth grade children who did not master properly the conventional writing yet. Based on the data generated by the research-action methodology, dialogues were established with some principles of the Historical-Cultural Theory on teaching, learning and development and with the assumptions of the Bakhtin Circle in relation to teaching through the genres of speech. It was concluded that, from the production of statements inserted in an extraverbal situation, the children appropriated the acts of writing.
Keywords: Teaching and learning of writing; Teacher contributions; Discourse genres